Innovative model for teaching entrepreneurship: an approach from business solutions - Mosquera - Carrascal, Adriana; Vergel - Quintero, Damarys; Bayona - Trillos, Ramón Armando (Universidad Francisco de Paula Santander, 2022)
The main objective is to present the research results of the Business Skills Training Plan carried out specifically in the Business Challenge activity, whose purpose is to promote the development of skills, competencies and skills of the students of the tenth semester of the Business Administration program, to provide a solution in a short time to a proposed business and experiential challenge. For this reason, the case methodology is used, which offers the opportunity to the participants to interact with certain situations, derived from the understanding of the organizations and their different variables, developing skills to face this type of realities. The results show that students develop business skills by providing solutions in correspondence to dynamics, where general knowledge comes to life and that, therefore, these solutions are not infallible, much less absolute. It is concluded that the pedagogical strategy bases the formation of this type of competences in the students, strengthening a context of soft skills, where the student develops decision-making capacity, leadership and teamwork.